COMPARATIVE EFFICIENCY OF TRAWLS MADE OF NYLON ,POLYETHYENE ,MONO FILAMENT AND TAPE TWINES. - KARTHA, K N; HRIDAYANATHAN, C; CECILY, P J (Fishery Technology, 2017)
Results cf comparative fishing operations conducted with three nets of identical cesign made of nylon, twisted polye- 1hylene monofilamenc and high ciensity polyethylene (HDPE) tape twines are presented in this communication. Since the tape net recorded the highest prawn and fish catch, monofilament and nylon following in order, it can be recommended to the fishing industry as one of the cheapest and effective fishing materials evolved for trawl fabrication.